2015
DOI: 10.1007/s00776-015-0705-9
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic ACL reconstruction: rectangular tunnel/bone–patellar tendon–bone or triple-bundle/semitendinosus tendon grafting

Abstract: Anatomic ACL reconstruction is the reasonable approach to restore stability without loss of motion after ACL tear. To mimic the normal ACL like a ribbon, our preferred procedures is the anatomic rectangular tunnel (ART) technique with a bone-patellar tendon-bone (BTB) graft or the anatomic triple bundle (ATB) procedure with a hamstring (HS) tendon graft. It is important to create tunnel apertures inside the attachment areas to lessen the tunnel widening. To identify the crescent-shaped ACL femoral attachment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 30 publications
0
47
0
Order By: Relevance
“…Recently, good clinical results of ART-BTB ACL reconstruction have been reported. 1 , 2 , 3 , 4 Moreover, it has been shown that the behavior of the reconstructed knee is close to the biomechanical behavior of the normal knee as compared with the conventional round-tunnel BTB ACL reconstruction. 4 …”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Recently, good clinical results of ART-BTB ACL reconstruction have been reported. 1 , 2 , 3 , 4 Moreover, it has been shown that the behavior of the reconstructed knee is close to the biomechanical behavior of the normal knee as compared with the conventional round-tunnel BTB ACL reconstruction. 4 …”
Section: Discussionmentioning
confidence: 79%
“…To avoid the risk of femoral posterior wall injury or nerve damage, the inside-out technique or the conventional outside-in technique (to drill from the bone cortex to the joint) is selected depending on whether knee flexion to 140° can be achieved. 3 In addition, performing the insertion of the guide pin twice raises the risk of prolonged operating time and technical error.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We de ned the femoral, tibial and bular attachment areas of the ACL, PCL, dMCL, sMCL and lateral collateral ligament (LCL) according to the osseous landmark and magnetic resonance imaging (MRI) [8,10,[23][24][25][26][27][28][29][30][31]. The accuracy of the attachment area is 0.7 ± 0.1 mm [31].…”
Section: Methodsmentioning
confidence: 99%
“…An ALB graft fixation was also performed using the same plate and screw. Three months after the initial surgery, an anatomical ACL reconstruction 2 using rectangular tunnel/bone-patellar tendon-bone was performed ( Fig. 3 ).…”
Section: Case Presentationmentioning
confidence: 99%